2021
DOI: 10.3389/fpsyg.2021.644337
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the COVID-19 Mental Health Crisis: A Perspective on Using Interdisciplinary Universal Interventions

Abstract: Mental health is reaching a crisis point due to the ramifications of COVID-19. In an attempt to curb the spread of the virus and circumvent health systems from being overwhelmed, governments have imposed regulations such as lockdown restrictions and home confinement. These restrictions, while effective for infection control, have contributed to poorer lifestyle behaviors. Currently, Positive Psychology and Lifestyle Medicine are two distinct but complimentary disciplines that offer an array of evidence-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 102 publications
0
18
0
1
Order By: Relevance
“…Nevertheless, more studies are required to assess the effectiveness of these interventions. Furthermore, universal digital mental health interventions are crucial to address the mental health of the population during lockdown and other restrictions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, more studies are required to assess the effectiveness of these interventions. Furthermore, universal digital mental health interventions are crucial to address the mental health of the population during lockdown and other restrictions [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that mental health interventions and support programs have improved mental health of the participants during medical crises [28][29][30]. Psychological, psychiatric, education and other interventions either in person or online have improved the mental health of individuals during COVID-19, Ebola, and SARS pandemics [29][30][31]. Nevertheless, more studies are required to assess the effectiveness of these interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Tan et al [ 69 ] asserts that the impact of small effect sizes can be large when translated to a population level. Hence, digital interdisciplinary MHPIs provide a potential strategy to deliver low-cost and scalable interventions to build the psychological resilience of an individual to help them cope with the adversities experienced in life [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are non-clinical, directed at entire populations, and they usually seek to address generic mental health risk and protective factors (Huppert, 2009;Purtle et al, 2019). Even though each psychological wellbeing intervention has its unique focus, they generally aim to promote mental wellness and often to destigmatise mental disorders through a combination of psychoeducation and focused content (Przybylko et al, 2021). In this way, psychological well-being approaches are much broader and less intensive than specialised mental health treatments.…”
Section: Psychological Well-being Interventionsmentioning
confidence: 99%